2021
DOI: 10.1161/circep.120.008867
|View full text |Cite|
|
Sign up to set email alerts
|

Positive Clinical Benefit on Patient Care, Quality of Life, and Symptoms After Contact Force–Guided Radiofrequency Ablation in Persistent Atrial Fibrillation

Abstract: Background: There is limited evidence on the long-term clinical benefits of catheter ablation in patients with persistent atrial fibrillation. Methods: PRECEPT was a prospective, multicenter, single-arm Food and Drug Administration–regulated investigational device exemption clinical study. Patients were followed up to 15 months after ablation. Outcomes included use of antiarrhythmic drugs, rate of cardioversions and cardiovascular hospitalization, Atria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Our findings regarding QOL, support previously published QOL data from several studies of patients with PersAF treated with various endocardial ablation strategies ( 10 , 12 ). In several studies, the improvements in QOL have been attributed to and associated with the reduction in AF burden ( 3 , 6 , 13 , 19 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings regarding QOL, support previously published QOL data from several studies of patients with PersAF treated with various endocardial ablation strategies ( 10 , 12 ). In several studies, the improvements in QOL have been attributed to and associated with the reduction in AF burden ( 3 , 6 , 13 , 19 ).…”
Section: Discussionsupporting
confidence: 91%
“…CA to isolate the pulmonary veins (PV) is effective in the treatment of patients with paroxysmal AF (i.e., AF that terminates within 7 days) ( 7 - 9 ). Recent investigational device exemption (IDE) clinical trials reported favorable outcomes following the use of cryoballoon and radiofrequency CA in the treatment of patients with early PersAF less than 6 months ( 10 ) and PersAF less than 12 months ( 11 ), with improvements in AF-related symptoms and QOL in post-procedure follow-up ( 10 , 12 ). Patients with persistent AF (PersAF) and longstanding PersAF (LSPAF) may tolerate their symptoms better than patients with paroxysmal AF because of living with the condition for a prolonged period.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies have shown a high reconnection rate when PWI was performed using a “box” lesion with 20 to 35 watts. In contrast to CAPLA, the PRECEPT study reported a single-procedure success rate in Pe-AF patients of 80.4% at 15 months, with subsequent improvement in the patients’ quality of life and reduction in hospitalization, which is likely to be due to the different ablation techniques used [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have reported a high reconnection rate when PWI is carried out using a “box” lesion set and low power (20–35 W). In contrast to CAPLA, the PRECEPT study reported a single-procedure success rate in Pe-AF of 80.4% at 15 months, with subsequent improvement in quality of life and a reduction in hospitalization, likely due to different ablation techniques [ 34 , 35 ]. Winkle et al reported a large real-world evaluation of the combination of HPSD and CF sensing catheters [ 36 ].…”
Section: Discussionmentioning
confidence: 99%